Effects of Cell Network Structure on the Strength of Additively Manufactured Stainless Steels - Kim, Jung Gi; Seol, Jae Bok; Park, Jeong Min; Sung, Hyokyung; Park, Sun Hong; Kim, Hyoung Seop (Metals and materials international, 2021)
The rapid melting and solidification cycle in additive manufacturing creates a non-equilibrium environment that induces metastable microstructures. These metastable microstructures include solute heterogeneity, dislocation cell structure and nano-sized precipitation, which contributes to the strength of additively manufactured alloys. Because the presence of metastable microstructure contributes to the mechanical property enhancement of additively manufactured alloy, quantification and estimation of strength by metastable microstructure becomes important issue. In this study, the role of dislocation cell structure on the mechanical property of additively manufactured stainless steels was investigated. The evolved cell networks not only interrupted dislocation gliding, but also acted as crack propagation paths during plastic deformation. The finer cell networks found in the additively manufacture 304L stainless steels induced more interactions with dislocations than those found in the additively manufacture 316L stainless steels, and that is related to the higher strength during tensile test. This result demonstrates the dislocation cell structure is a main strengthening mechanism for additively manufactured materials and the modified Hall–Petch hardening model successfully estimate the strengthening by cell boundaries. Graphic Abstract